U. PILULIFERA MIMICS THE ACTION OF METFORMIN IN LOWERING LIVER ENZYMES IN ALLOXAN DIABETIC MODEL - Ahed J AlKhatib; Ilham A AlKhatib; M. A. Sulaiman; S. M. Shuaibu; Mosleh A Alkhatatbeh; M. Abdulhadi; A. B. Maikano; Bader Salem Alanazi; Fatima Laiche (European Scientific Journal, ESJ, 2014)
Liver plays a significant role in glucose homeostasis and acts to retain normal glucose levels during fasting and in the postprandial period. The association between liver function tests and incidence of diabetes is not well established. The present study was conducted to investigate the association between liver enzymes and diabetes, and to investigate the effects of the extract of U. pilulifera and metformin on liver enzymes. Study methodology included collection of U. pilulifera, preparation of its extract, induction of diabetic model through alloxan injection. Study findings showed a positive relationship between studied liver enzymes ALT, AST, and ALP and diabetes. Treating diabetic groups using either the extract of U. pilulifera or metformin showed protection potential for liver through restoring liver enzymes to levels approximate to control groups. Taken together, the extract of U. pilulifera mimics the action of metformin in treating diabetes through restoring liver function tests to levels approximate to control group.